EFFICACY OF REALITY THERAPY ON SUICIDAL IDEATION AMONG IN-SCHOOL ADOLESCENTS WITH DIFFERENT PARENT SOCIO-ECONOMIC STATUS IN ABUJA MUNICIPAL AREA COUNCIL - GIWA-AMU, Faith Osedebamen Clara; OAIKHENA , 2KINGSLEY (Sokoto Educational Review, 2025)
The study investigated the Efficacy of Reality Therapy in the management of Suicidal Ideation among in-school Adolescents in Abuja Municipal Area Council. It also examined the interaction effect of treatment by Parents’ Socio-Economic Status on Suicidal Ideation. Two research questions and hypotheses were raised to guide the study. Quasi-Experimental research design method was adopted. The population was 12,400 with a sample size of 44 students. An adapted instrument, Suicidal Ideation Questionnaire for in-school Adolescents, was used for data collection with a reliability co-efficient of 0.92 that was obtained using the Cronbach Alpha statistics. Data were analysed with descriptive statistics, paired sample t-test, and Analysis of Variance. Findings showed that Reality Therapy was effective on Suicidal Ideation among in-school Adolescents, and there was no significant interaction effect by Parents’ Socio-Economic Status on Suicidal Ideation. It was then recommended that counselling psychologists should adapt this therapy to assist students with suicidal thoughts and behaviours. DOI: https://doie.org/10.10318/SER.2025133426